Tunable coupling by means of oxygen intercalation and removal at the strongly interacting graphene/cobalt interface. (15th August 2020) - Jugovac, Matteo; Genuzio, Francesca; Menteş, Tevfik Onur; Locatelli, Andrea; Zamborlini, Giovanni; Feyer, Vitaliy; Schneider, Claus Michael
Abstract: It is well known that intercalated species can strongly affect the graphene-substrate interaction. As repeatedly shown by experiment and theory, the intercalation of atomic species may establish a free-standing character in chemisorbed graphene systems. Here, we focus on graphene grown on a strongly interacting support, cobalt, and demonstrate that the film electronic structure and doping can be tuned via the intercalation/removal of interfacial oxygen. Importantly, cathode lens microscopy reveals the main mechanism of oxygen intercalation, and in particular how microscopic openings in the mesh enable oxygen accumulation at the graphene-cobalt interface. Our experiments show that this process can be carefully controlled through temperature, without affecting the film morphology and crystalline quality. The presence of oxygen at the interface induces an upward shift of the graphene π band, moving its crossing above the Fermi level, accompanied by an increased Fermi velocity and reduced momentum width. Control on the graphene coupling to cobalt may enable one to alter the induced spin polarization in graphene's electronic states. Graphical abstract: Image 1